The Implications of Rewards for Students’ Learning Motivation in EFL Classrooms - Rina Nurdiani Salam; Maemuna Muhayyang; Muhammad Miftah Fauzan (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This research discusses the implications of various types of rewards for students’ intrinsic and extrinsic motivation in English as a foreign language (EFL) classrooms. This research employed a qualitative descriptive design through classroom observation, interviews, and documentations at SMP Negeri 3 Watampone. The subjects of the research were an English teacher and students from class VIII C and IX B. The data were analyzed through data reduction, data display, and conclusion drawing. The result found that reward verbal and non-verbal such as praise, gesture, proximity and fun activity, strengthened students’ intrinsic motivation by improving their confidence reducing their anxiety, and encouraging long-term engagement in learning. Meanwhile, non-verbal rewards, such as objects and symbols were effective in stimulating extrinsic motivation by encouraging students’ participation and task completion. However, excessive dependence on rewards may shift students’ focus from the learning process to obtaining rewards. This research concludes that non-verbal rewards such as physical objects and symbols are effective primarily as short-term motivation triggers. In contrast, verbal and non-verbal rewards like praise, gestures, and proximity play a more significant role in maintaining students' intrinsic motivation and long-term engagement in EFL learning.